2017
DOI: 10.1039/c6ra26920f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the growth morphology of explosive crystals in solution: insights from solvent behavior at the crystal surface

Abstract: The solvent effect on the growth morphology of an explosive crystal was explored by deciphering the molecular interactions at the crystal–solvent interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The binding affinity of the solvent (acetone) varies with the crystal faces in the following order: (002) ≈ (210) > (200) > (020) > (111). These results also showed good agreement with the experimental RDX morphology grown in acetone . Experimental studies conducted by Van der Heijden et al revealed that the change in morphology of particles of RDX, HMX, and CL-20 was due to the interaction between solvent and growth faces, variations in supersaturation, and presence of impurities .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The binding affinity of the solvent (acetone) varies with the crystal faces in the following order: (002) ≈ (210) > (200) > (020) > (111). These results also showed good agreement with the experimental RDX morphology grown in acetone . Experimental studies conducted by Van der Heijden et al revealed that the change in morphology of particles of RDX, HMX, and CL-20 was due to the interaction between solvent and growth faces, variations in supersaturation, and presence of impurities .…”
Section: Resultssupporting
confidence: 86%
“…These results also showed good agreement with the experimental RDX morphology grown in acetone. 50 Experimental studies conducted by Van der Heijden et al revealed that the change in morphology of particles of RDX, HMX, and CL-20 was due to the interaction between solvent and growth faces, variations in supersaturation, and presence of impurities. 12 They concluded that with the increase of supersaturation above 40%, particles with random orientations were formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen investigated the solvent effects of acetone (AC) and cyclohexanone (CYC) on the crystal morphology of 1,3,5‐trinitro‐1,3,5‐triazinane (RDX) with the modified attachment energy (MAE) model through molecular dynamic (MD) simulations. In order to understand the AC solvent effects on the RDX crystal morphology, Liu studied the growth of the ctystal at the molecular level . The AC and acetonitrile (ACN) solvent effects on the crystal morphology of octahydro‐1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine (HMX) were simulated by adopting MAE models.…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the exposed surface for a given load catalyst at the nanoscale, metal nanoparticles have been widely employed in a wide range of catalytic systems [16][17][18] . In particular, the growth process of polyhedral crystals has been explored with significant interest not only due to the emergence of new or enhanced properties from selected crystal surfaces, but also due to the opportunity for fundamental studies on the control nucleation and growth kinetics involved along the crystallization mechanism 19 .…”
Section: Morphology That Mattersmentioning
confidence: 99%